PENGARUH ECO ENZYME PROJECT DALAM MENINGKATKAN ECOLITERACY ANAK USIA 5-6 TAHUN - Dihya Azziyadatur Latifah; Melia Dwi Widayanti; Fatiha Khoirotunnisa Elfahmi; Sri Widayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of implementing the Eco enzyme project on early childhood ecoliteracy behavior, particularly in the behavioral aspect. The research was conducted at TK Kurnia Wonorejo in Group B with a total of 26 children, using a pre-experimental method with a one-group pretest–posttest design. Data were collected through behavioral observation using a frequency rating scale instrument that had been tested for validity and reliability. The treatment was conducted in four sessions through a series of Eco enzyme project activities, including the introduction of environmental concepts, eco enzyme production, observation of the fermentation process, and filtering and utilizing the eco enzyme results. The normality test indicated that the data were not normally distributed; therefore, data analysis was continued using the Wilcoxon Signed Ranks Test. The analysis results showed a significance value of 0.004 (p < 0.05), indicating a significant difference in children's ecoliteracy behavior before and after the treatment. Behavioral improvement was observed across all assessed items, with the most notable increase in children’s behavior of reminding peers to maintain environmental cleanliness. Thus, the Eco enzyme project has a positive effect on improving early childhood ecoliteracy behavior and can serve as a contextual and meaningful learning activity.